Beta-neurexin is a ligand for the Staphylococcus aureus MSCRAMM SdrC - FOSTER, TIMOTHY JAMES (My University, 2010)
Gram-positive bacteria contain a family of surface proteins that are covalently anchored to the cell wall of the organism. These cell-wall anchored (CWA) proteins appear to play key roles in the interactions between pathogenic organisms and the host. A subfamily of the CWA has a common structural organization with multiple domains adopting characteristic IgG-like folds. The identified microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) belong to this subfamily, as does SdrC from S. aureus. However, an interactive host ligand for the putative MSCRAMM SdrC was not previously identified. We have screened a phage display peptide library and identified a peptide sequence found in beta-neurexin that binds SdrC. A synthetic peptide corresponding to the identified sequence as well as a recombinant form of the beta-neurexin 1 exodomain binds SdrC with high affinity and specificity. Furthermore, expression of SdrC on bacteria greatly enhances microbial adherence to cultured mammalian cells expressing beta-neurexin on their surface. Taken together, our experimental results demonstrate that beta-neurexin is a ligand for SdrC. This interaction involves a specific sequence located in the N-terminal region of the mammalian protein and the N(2)N(3) domain of the MSCRAMM. The fact that these two proteins interact when expressed on the appropriate cells demonstrates the functionality of the interaction. Possible implications of this interaction are discussed.
PUBLISHED
Keywords: Microbiology